Misconceptions and paradoxes in soil-transmitted helminthiases control as a public health problem. - Alejandro J Krolewiecki (Public Library of Science (PLoS), 2018)
Soil-transmitted helminthiases (STHs) constitute a public health problem that requires immediate action to resolve the morbidity of those harboring the parasites in their guts, to prevent infection in all those at risk, and to interrupt the vicious circle of poverty and disease in the affected communities, structural poverty being the main determinant of this group of infectious diseases. Since the times of the Rockefeller initiatives over a hundred years ago, the strategy has been viewed as one requiring community-wide efforts rather than pure individual case management. The World Health Organization (WHO) and its regional offices, as the governing institutions endorsed by the countries and their governments, have been the leaders in stating the actual executive measures to reach the goals and endpoints for the management of the problem. With the task of setting a group of activities that could be launched, monitored, and measured, these actions were established with the available resources since this public health problem had to be launched immediately, resources were those available at the moment and not those appearing on a wish list. Considerable progress has been made in the establishment of policies for the achievement of the Millennium Development Goals (MDGs), later followed by the Sustainable Development Goals (SDGs) through WHO-lead actions for the control of neglected tropical diseases (NTDs). With an initial goal of morbidity control, there are already discussions and proposals for elimination of STH if support is sustained and empiric facts confirm data emerging from modeling and small-scale studies. The aim of these comments is to describe and question instances of currently accepted concepts, theories, and practices that conform to the dogmatic status quo that serves as the foundation on top of which the new elimination aspirations are supposed to be built on, which might not be serving the desired purpose if taken unrevised.